2006
DOI: 10.1523/jneurosci.2967-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Listening in Silence Activates Auditory Areas: A Functional Magnetic Resonance Imaging Study

Abstract: Directing attention to some acoustic features of a sound has been shown repeatedly to modulate the stimulus-induced neural responses. On the contrary, little is known about the neurophysiological impact of auditory attention when the auditory scene remains empty. We performed an experiment in which subjects had to detect a sound emerging from silence (the sound was detectable after different durations of silence). Two frontal activations (right dorsolateral prefrontal and inferior frontal) were found, regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
86
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 51 publications
13
86
0
Order By: Relevance
“…Activity within the auditory system resembling the activity elicited by actual stimulation has also been reported in literature that did not focus on omissions within a sound sequence but during silence gaps in familiar musical pieces (Kraemer, Macrae, Green, & Kelley, 2005), violations in learned motor-auditory or visuo-auditory coupling (Stekelenburg & Vroomen, 2015;SanMiguel, Widmann, Bendixen, Trujillo-Barreto, & Schroger, 2013), or attention to auditory events (Voisin, Bidet-Caulet, Bertrand, & Fonlupt, 2006). However, the literature so far suffers two main limitations.…”
Section: Introductionmentioning
confidence: 77%
“…Activity within the auditory system resembling the activity elicited by actual stimulation has also been reported in literature that did not focus on omissions within a sound sequence but during silence gaps in familiar musical pieces (Kraemer, Macrae, Green, & Kelley, 2005), violations in learned motor-auditory or visuo-auditory coupling (Stekelenburg & Vroomen, 2015;SanMiguel, Widmann, Bendixen, Trujillo-Barreto, & Schroger, 2013), or attention to auditory events (Voisin, Bidet-Caulet, Bertrand, & Fonlupt, 2006). However, the literature so far suffers two main limitations.…”
Section: Introductionmentioning
confidence: 77%
“…Overall enhancement of human auditory cortex activity by selective attention has been shown by functional MRI (Grady et al, 1997;Jancke et al, 1999Jancke et al, , 2003Rama & Courtney, 2005;Voisin et al, 2006), PET (Zatorre et al, 1999;Hugdahl et al, 2000;Alho et al, 2003;Johnson & Zatorre, 2005), EEG (Hillyard et al, 1973) and MEG (Woldorff et al, 1993;Ozaki et al, 2004;Ahveninen, et al, 2006). Auditory attention can selectively be directed to a rich variety of features including spatial location, auditory pitch, frequency or intensity, to tone duration or FM direction or slope, to speech vs. nonspeech streams.…”
Section: I3 Neural Locus Of Auditory Attentionmentioning
confidence: 98%
“…Other association cortical areas in the attentional network (Posner and Peterson, 1990) are also activated in auditory attention -such the posterior parietal cortex (Cohen et al, 2005;Yantis, 2004, 2006), and right inferior frontal and dorsolateral prefrontal cortex (Voisin et al, 2006). Moreover, neuroimaging studies of the thalamus (Frith and Friston, 1997) and physiological (McAlonan et al, 2006) and neuroanatomical (Sakoda et al, 2004) studies of the thalamic reticular nucleus suggest that the different thalamic nuclei may play important roles in attentional modulation and in helping direct the shifting focus of attention (Crick, 1984).…”
Section: I3 Neural Locus Of Auditory Attentionmentioning
confidence: 99%
“…The primary auditory cortex of healthy subjects seems to have "a propensity to spontaneously 'activate' during silence" (Hunter et al, 2006). Primary auditory cortex activation in the absence of auditory input has been found for short gaps of silence (lasting 2-5 s) that were inserted at different points during the soundtrack of familiar music (Kraemer et al, 2005) and in a sound detection task during the preceding silence of the emerging sounds (Voisin et al, 2006). A further report of primary auditory activation during mental imagery of a computer generated monotone (C maj ) comes from Yoo and colleagues (Yoo et al, 2001) but a recent inspection of the exact locus of activation indicated in that study questioned their results (Halpern et al, 2004).…”
Section: Introductionmentioning
confidence: 99%